Endometriosis - A Medical Challenge: Impact on Fertility and Treatment Method - Zwierzchowska, Maria; Stachowiak, Julia; Sosin, Julia; Pilarz, Anna; Sojka, Aleksandra; Salamon, Dariusz; Domagała, Wojciech (Quality in Sport, 2024)
Aim of study: The subject of this review is to highlight the complexity of the disease known as endometriosis. This disease affects 10% of women of reproductive age, causing a number of symptoms of various origins, and additionally affects women’s fertility, mental health and role in society. The work aims to systematize knowledge about endometriosis, the mechanism by which it affects fertility and possible therapies, including surgical methods and assisted reproductive technology (ART.). The issue of infertility associated with endometriosis is has not been fully explored yet. A personalized treatment plan including medication, surgical assisted reproductive techniques and psychological support should be developed to improve the quality of life of patients with endometriosis and enable them to become pregnant. Material and methods: A systematic review of scientific and medical literature from the PubMed and Google Scholar databases was conducted. Results: Currently, the most effective treatment for infertility is in vitro fertilization (IVF). Successful treatment of endometriosis-related infertility should be discussed in detail with each patient and the decision on the therapy plan should be individual and comprehensive. Keywords: endometriosis, infertility, chronic pelvic pain, gynecology, IVF, IVI